2018
DOI: 10.1111/clr.13143
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of cone beam computed tomography in assessing peri‐implant bone loss: A systematic review

Abstract: In vitro, CBCT performs well in detecting peri-implant circumferential-intrabony or fenestration defects but less in depicting dehiscences. Influencing factors due to other site-related and technical parameters on the diagnostic outcome need to be addressed further in the future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 83 publications
(241 reference statements)
0
33
0
Order By: Relevance
“…For very thin structures less than 0.5 mm thick, however, the accuracy of CBCT is limited (Fienitz et al, ). A systematic review reported both over‐ and underestimation of linear CBCT measurements for peri‐implant bone assessments (Pelekos, Acharya, Tonetti, & Bornstein, ). It must, therefore, be emphasized that the absolute values of our linear measurements, which are within the 1‐mm range, might be biased by global errors.…”
Section: Discussionmentioning
confidence: 99%
“…For very thin structures less than 0.5 mm thick, however, the accuracy of CBCT is limited (Fienitz et al, ). A systematic review reported both over‐ and underestimation of linear CBCT measurements for peri‐implant bone assessments (Pelekos, Acharya, Tonetti, & Bornstein, ). It must, therefore, be emphasized that the absolute values of our linear measurements, which are within the 1‐mm range, might be biased by global errors.…”
Section: Discussionmentioning
confidence: 99%
“…35 CBCT also showed a limited accuracy measuring vestibular and lingual bone levels. 36 The ex vivo studies (cadaver models) demonstrated good values for sensitivity and specificity for both circumferential and infraosseous defects but lower for dehiscences. 15 The diagnostic outcomes of CBCT imaging of peri-implant bone loss have been related to the type of study and defect morphology.…”
Section: Agreements and Disagreements With Previous Studiesmentioning
confidence: 92%
“…15 The diagnostic outcomes of CBCT imaging of peri-implant bone loss have been related to the type of study and defect morphology. 36 The ex vivo studies (cadaver models) demonstrated good values for sensitivity and specificity for both circumferential and infraosseous defects but lower for dehiscences. 37,38 Contrastingly, CBCT imaging for defect analysis in in vivo animal studies showed positive correlation with histology but have a tendency to over- 17,34 or under-estimate 15,39 the size of the defect.…”
Section: Reliability Of Cone-beam Computed Tomography (Cbct) To Assmentioning
confidence: 92%
“…CBCT can also have a relevant role in the determination of defect morphology, and it may play an essential role in therapeutic decision making. 24 Anatomically, peri-implant defects can be grouped similar to periodontal osseous defects, thus being primarily classified as "suprabony/horizontal" or "intrabony/vertical." Intrabony/ vertical defects can further be categorized as a one-, two-, or three-walled defect (►Fig.…”
Section: Infectionmentioning
confidence: 99%